2020
DOI: 10.1016/j.cmi.2020.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between antiretroviral therapy and complementary and alternative medicine: a narrative review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 88 publications
1
14
0
3
Order By: Relevance
“…51 However, numerous studies indicate that supplementation with garlic or its derivatives could exert an undesirable interaction with prescribed antiretroviral drugs against HIV disease. 52,53…”
Section: Biological Activity Of Garlicmentioning
confidence: 99%
“…51 However, numerous studies indicate that supplementation with garlic or its derivatives could exert an undesirable interaction with prescribed antiretroviral drugs against HIV disease. 52,53…”
Section: Biological Activity Of Garlicmentioning
confidence: 99%
“…However, there is no positive correlation between the supplementation of vitamin C and a reduction in oxidative stress [ 82 , 83 ]. It has also been suggested that daily use of 1000 mg of vitamin C for 7 days appears to induce certain hepatic cytochromes, including cytochrome P450 3As (CYP3As), which leads to a decrease in the Cmax of indinavir by 20% [ 84 ]. More studies and trials are needed to draw a conclusion on the benefits of vitamin C on disease progression and prognosis of HIV infection.…”
Section: Role Of Nutraceuticals/dietary Agents In Alleviating Neurolo...mentioning
confidence: 99%
“…Ginkgolic acid (GA) produced by GB can act as an inhibitor against HIV and other enveloped viruses through the inhibition of protease activity [ 86 , 87 ]. GA is also widely used as a natural therapeutic agent to improve memory and treat conditions such as hemorrhoids, dementia, and depression [ 84 ].…”
Section: Role Of Nutraceuticals/dietary Agents In Alleviating Neurolo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The causality evaluation is further complicated when the suspected adverse reactions are associated with multicomponent products. Moreover, people often use dietary supplements along with conventional drugs, with the potential risk of pharmacological interactions (Bordes et al, 2020;Chrubasik-Hausmann, Vlachojannis, & McLachlan, 2019). At last, the possible presence of undeclared ingredients, or quality issues, could increase the safety concerns (Ekar & Kreft, 2019).…”
mentioning
confidence: 99%